Enhanced electromechanical properties of natural rubber via the synergistic effect of poly(catechol/polyamine) modification and Ag deposition on TiO2 nanoparticles. (15th June 2022) - Yu, Liyuan; Yang, Dan
Abstract: Owing to their fast response, high efficiency, and large deformation, dielectric elastomer actuators (DEAs) are promising candidates for application in the fields of artificial muscles, sensors, and soft robots. With the aid of the large actuated strains of natural rubber (NR) at a relatively low driving voltage, titanate oxide (TiO2 ) nanoparticles (NPs) modified by poly(catechol/polyamine) (PCPA) and deposited by Ag NPs were prepared (labeled as TiO2 –PCPA–Ag). Due to the synergistic effect of the enhanced interfacial polarization obtained through PCPA modification and Ag NP micro-capacitors, the dielectric constant of the TiO2 –PCPA–Ag–NR composites increased. In addition, the flexible PCPA endowed the composites with low elastic modulus, resulting in enhanced electromechanical properties. Thus, the NR composites filled with 10 phr TiO2 –PCPA–Ag NPs exhibited the highest actuated strain of 8.86% at an electric field of 55.94 kV/mm, which is 2.1 times of pure NR (4.30%) at 55 kV/mm. The design of the NR composites proposed in this work via the synergistic effect of an organic layer and metal NPs will play a guiding role in the preparation of novel DEAs, which could meet future requirements for the development of actuators. Graphical abstract: Natural rubber composites with enhanced electromechanical properties were prepared by incorporating titanate oxide nanoparticles via the synergistic effect of poly(catechol/polyamine) modification and Ag nanoparticles. Image 1